Malaria Caused by Plasmodium Vivax: A Case Report with Thrombocytopenia - Boris, Roy; Purnama, Asep (Jurnal Indonesia Sosial Sains, 2026)
Malaria is an infectious disease that can be life-threatening and remains a major public health problem to this day. One contributing factor is the high number of imported malaria cases, which has led to the emergence of new cases in areas classified as low-endemic and even in malaria elimination settings. This case report aims to describe an imported malaria case accompanied by thrombocytopenia in a low-endemic area. Case Report: A 38-year-old male presented with complaints of high fever that had subsided one week prior to hospital admission. The patient had previously lived for one month in Papua and had returned to East Nusa Tenggara (NTT) one week before presentation. Laboratory examinations revealed thrombocytopenia and Plasmodium vivax infection. The patient received treatment for four days, consisting of dihydroartemisinin–piperaquine for three days and primaquine. On the fourth day of treatment, the patient reported no complaints, platelet counts improved, and microscopic blood examination showed no presence of Plasmodium vivax. The patient was discharged and advised to continue primaquine therapy at home and to attend follow-up visits at the internal medicine clinic. This case highlights the importance of strengthening epidemiological investigation programs using the 1-2-5 strategy, particularly in low-endemic and malaria-elimination areas. It also emphasizes that malaria should not be excluded from the differential diagnosis in patients presenting with fever and thrombocytopenia, especially in individuals with a history of travel to endemic regions.